2009
DOI: 10.1155/2009/864564
|View full text |Cite
|
Sign up to set email alerts
|

A Robust and Self‐Paced BCI System Based on a Four Class SSVEP Paradigm: Algorithms and Protocols for a High‐Transfer‐Rate Direct Brain Communication

Abstract: In this paper, we present, with particular focus on the adopted processing and identification chain and protocol-related solutions, a whole self-paced brain-computer interface system based on a 4-class steady-state visual evoked potentials (SSVEPs) paradigm. The proposed system incorporates an automated spatial filtering technique centred on the common spatial patterns (CSPs) method, an autoscaled and effective signal features extraction which is used for providing an unsupervised biofeedback, and a robust sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 21 publications
1
67
1
1
Order By: Relevance
“…The learning effect on communication performances, mental workload and user satisfaction should also be part of future researches. The accuracies obtained in patients are lower than those presented by (1) Parini et al [35] on patients with Duchenne muscular dystrophy using a four-class overt SSVEP-BCI and (2) Combaz et al [36] using an overt SSVEP speller in patients with incomplete LIS. Kübler and Birbaumer tested a visual P300 speller with patients [37].…”
Section: Discussioncontrasting
confidence: 59%
“…The learning effect on communication performances, mental workload and user satisfaction should also be part of future researches. The accuracies obtained in patients are lower than those presented by (1) Parini et al [35] on patients with Duchenne muscular dystrophy using a four-class overt SSVEP-BCI and (2) Combaz et al [36] using an overt SSVEP speller in patients with incomplete LIS. Kübler and Birbaumer tested a visual P300 speller with patients [37].…”
Section: Discussioncontrasting
confidence: 59%
“…There had been many supervised classification methods, such as DLSVQ, LAS and joint time-frequency analysis (JTFA) (Müller-Putz et al, 2005;Parini et al, 2009), proposed and utilized for SSVEPbased BCI systems. The recognition accuracy by our approach was nearly equal to those of these algorithms.…”
Section: Parametersmentioning
confidence: 99%
“…This signal is often extracted noninvasively from electroencephalography (EEG) for brain computer interfaces (BCIs). Recent studies indicated that SSVEPs had higher classification accuracy than other EEG patterns, such as P300 and event-related desynchronization/synchronization (ERD/ERS) Parini et al, 2009;Guger et al, 2012). And a great number of SSVEP-based BCIs had been developed for human-computer communication (Wolpaw et al, 2000(Wolpaw et al, , 2002Moore, 2003;Kelly et al, 2005;Xia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Progressive improvements in the design have produced systems that allow for impressive rate of communication. Parini et al [97] showed performance results from a SSVEP-based BCI that employed four cubic LED stimuli mounted at each side of a display. Seven healthy participants and four patients affected by muscular dystrophy at different stages were able to successfully use this system.…”
Section: Ssvep-based Bcismentioning
confidence: 99%